INFLUENCE OF CULTIVARS AND DRYING METHODS ON THE PHYSICOCHEMICAL AND FUNCTIONAL PROPERTIES OF AMBIENT STORED GREEN CHILLI POWDER (Applied Biological Research, 2026)
Dehydration of green chillies is a highly effective preservation technique that reduces moisture content, enhances storability, and ensures year-round availability, particularly in tropical and subtropical regions. This study evaluated the influence of three cultivars namely ‘Beldanga’, ‘Bidhan Chilli-4’, and ‘Bullet’ on the physicochemical and functional properties of green chilli powder (GCP) produced using different drying methods under ambient storage conditions (21-39°C and 42–93% relative humidity). The drying treatments included: sun drying for 8 ± 1 days; hot air drying at 60°C for 48 ± 1 h; osmotic treatment in 30% salt solution for 120 min followed by hot air drying at 60°C for 30 ± 1 h; and osmotic treatments in 30% salt: sugar (3:1) and 30% salt: vinegar (3:1) solutions, each followed by hot air drying at 60°C for 30 ± 1 h. The results showed GCP had low moisture content (9.50%), low bulk density (470 kg m⁻³), relatively high tapped density (690 kg m⁻³), and poor flowability (Carr index: 28.78%), depicting a compact and highly compressible powder structure. These properties remained stable even after 180 days of ambient storage. Among the cultivars, ‘Bidhan Chilli-4’ demonstrated superior quality attributes. Hot air drying proved most effective processing method, followed by osmotic pre-treatment combined with hot air drying using salt + sugar (3:1) and salt + vinegar (3:1) solutions. Overall, the findings emphasize that careful cultivar selection and optimized drying techniques are critical for preserving the quality and nutritional value of GCP during extended storage.
Keywords: Ambient storage, cultivar, drying techniques, green chilli powder, quality attributes